2007
DOI: 10.1016/j.vaccine.2007.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Priming with SARS CoV S DNA and boosting with SARS CoV S epitopes specific for CD4+ and CD8+ T cells promote cellular immune responses

Abstract: Cellular immune response plays an important role in antiviral immunity. In our previous study, immunization of mice with severe acute respiratory syndrome coronavirus (SARS CoV) spike (S) DNA vaccine could induce both humoral and cellular immunity in response to a pool of entire overlapping S peptides. Identification of functional dominant epitopes in SARS CoV S protein for T cells is crucial for further understanding of cellular immune responses elicited by SARS CoV S DNA vaccine. In present study, mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 40 publications
3
71
0
Order By: Relevance
“…In view of the advantages of polypeptide vaccine, many teams are trying to identify SARS S epitopes to provide optimum candidates for vaccine development. We have identified two novel epitopes which could induce antigen-specific CD4 + T cell and CD8 + T cell immune responses in BABL/C mice, respectively [18]. However, it is known that the ultimate purpose of scientific research is used by human beings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the advantages of polypeptide vaccine, many teams are trying to identify SARS S epitopes to provide optimum candidates for vaccine development. We have identified two novel epitopes which could induce antigen-specific CD4 + T cell and CD8 + T cell immune responses in BABL/C mice, respectively [18]. However, it is known that the ultimate purpose of scientific research is used by human beings.…”
Section: Discussionmentioning
confidence: 99%
“…And to respiratory syncytial virus (RSV) infection, CTLs not only contribute to virus elimination, but also induce immunopathology [15,16]. Excited to us, we found that SARS-CoV S specific CTL responses were detected in patients who had recovered from SARS and mouse model [17,18]. Therefore, CTLs may determine the role of immunity in controlling viral pathogenesis.…”
Section: Introductionmentioning
confidence: 97%
“…tive approaches [9][10][11][12]. With regard to SARS-CoV, there have been many T cell epitopes identified by us and other groups [13][14][15][16][17][18]. In our previous study, we have identified five epitopes for CD8 + T cells in HLA-A*0201 transgenic mouse by "DNA prime, peptide boost" strategy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed SARS vaccines are of various categories (18), including inactivated virus vaccines (49,51,59), subunit vaccines (2,26), DNA vaccines (28,42,55), virus-like particles (40,41), viral vector-based vaccines (4,19,34), and different vaccine combinations (16,30,53). A variety of SARS vaccines have been tested in animals, including monkeys, ferrets, mice, and hamsters (1,7,9,20,33,48,49), and some of them have been evaluated in humans (42).…”
Section: Introductionmentioning
confidence: 99%